Description of Motivation, Knowledge, Attitudes, Perceptions, Cognition of Mothers in Nonpharmacological Pain Management due to Invasive Procedures in Children at Islamic Hospital in Surabaya - Santy, Wesiana Heris; Ugrasena, I Dewa Gede; Hidaayah, Nur; Utami, Resti (International Journal of Psychosocial Rehabilitation, 2020)
Invasive procedures and being in a hospital can be painful and frightening experience for children and their parents. Pain is a condition that must be treated immediately, other than being unethical to leave the patient in a state of pain. The ability of a family is still low and can lead to minimal nonpharmacological pain management which can lead to negative psychophysiological effects, increased health costs and increased chronic pain syndromes that are in line with the child’s response to the experience of pain in the future. This study aims to describe the mother’s internal factors in nonpharmacological pain management due to invasive procedures in children at the Islamic Hospital in Surabaya. The study design was descriptive, cross-sectional with a sample of 96 respondents with purposive sampling. Research analysis with frequency distribution. The results showed mothers had 100% positive motivation, 54% good knowledge, 99% attitude positive, 66% negative perception, mother cognitive 55% very confident belief they can treat children who experience pain. High motivation, good knowledge, positive attitude, cognitive are very confident but negative perceptions about the nonpharmacological pain management ability. All internal factors of the mother have a positive value so this proves that the mother has good motivation, knowledge, attitude and cognition to be involved in dealing with pain in her child when an invasive action is taken. Nurses must be sure to involve mothers in nonpharmacological interventions to overcome pain in children who undergo out invasive procedures when hospitalized.